2002
DOI: 10.1042/cs1020297
|View full text |Cite
|
Sign up to set email alerts
|

The role of inducible nitric oxide synthase in lipopolysaccharide-mediated hyporeactivity to vasoconstrictors differs among isolated rat arteries

Abstract: We investigated whether organ-specific differences exist in the role of inducible nitric oxide synthase (iNOS) in hyporeactivity to vasoconstrictors following 20 h in vitro exposure of isolated superior mesenteric, renal, hepatic and coronary arteries from the rat to bacterial lipopolysaccharide (LPS). LPS attenuated contraction in response to depolarizing KCl in all arteries. Maximum contractile responses to noradrenaline were attenuated in superior mesenteric and hepatic arteries, and those to the thromboxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As aforementioned, renal vasoconstriction and decreased GFR are two of the major mechanisms that lead to acute renal failure during sepsis (8)(9)(10). Previous reports indicated that endotoxemia-induced decreases in GFR would happen within hours after LPS exposure and would deteriorate even further if intervention was not installed (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, renal vasoconstriction and decreased GFR are two of the major mechanisms that lead to acute renal failure during sepsis (8)(9)(10). Previous reports indicated that endotoxemia-induced decreases in GFR would happen within hours after LPS exposure and would deteriorate even further if intervention was not installed (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Renal vasoconstriction and decreased glomerular filtration rate (GFR) are two of the major mechanisms that lead to acute renal failure during sepsis (8)(9)(10). Previous studies indicated that the decrease in GFR after sepsis is related to local inhibition of glomerular endothelial NOS (eNOS) by overproduced NO generated by sepsis-induced iNOS (10)(11)(12).…”
mentioning
confidence: 99%
“…In addition to variability between experimental regimes, both the pattern of the LPS-induced changes in vascular reactivity and the contribution of inducible NO synthase to the impaired vascular constriction differ between vascular beds (Piepot et al, 2002). Thus, at the level of resistance arteries, it remains unclear how significant hyporeactivity is, and the mechanism(s) responsible.…”
Section: Introductionmentioning
confidence: 99%
“…The arteriole was exposed to buffer, L-NAME (100 M), or aminoguanidine (100 M), which was introduced in a side branch between the aortic segment and the arteriolar bath (Fig. 2) [11]. At t ϭ 60 min, segments of aorta and arteriole were superfused with 2.5 g/ml Salmonella enteritidis endotoxin (Sigma Chemical Co., St. Louis, MO) or Krebsbicarbonate-HEPES buffer solution for 60 min or t ϭ 120 min.…”
Section: Experiments and Methodsmentioning
confidence: 99%